Insight into Helicase Mechanism and Function Revealed through Single-Molecule Approaches - Yodh, Jaya G. (2010)
Helicases are a class of nucleic acid motors that catalyze NTP-dependent unwinding of nucleic acid duplexes into single-strands, a reaction essential to all areas of nucleic acid metabolism. In the last decade, single-molecule technology has proven to be highly useful in revealing mechanistic insight into helicase activity that is not always detectable via ensemble assays. A combination of methods based on fluorescence, optical and magnetic tweezers, and flow-induced DNA stretching have enabled the study of helicase conformational dynamics, force-generation, step-size, pausing, reversal, and repetitive behaviors during translocation and unwinding by helicases working alone and as part of multi-protein complexes. The contributions of these single-molecule investigations to our understanding of helicase mechanism and function will be discussed.